Estradiol-independent restoration of T-cell function in post-reproductive females - King, Tristin L.; Bryner, B. Shaun; Underwood, Kaden B.; Walters, McKenna R.; Zimmerman, Shawn M.; Johnson, Nathan K.; Mason, Jeffrey B. (Frontiers in Endocrinology, 2023)
Abstract Aging leads to a general decline in protective immunity. The most common age-associated effects are in seen T-cell mediated immune function. Adult mice whose immune systems show only moderate changes in T-cell subsets tend to live longer than age-matched siblings that display extensive T-cell subset aging. Importantly, at the time of reproductive decline, the increase in disease risks in women significantly outpace those of men. In female mice, there is a significant decline in central and peripheral naïve T-cell subsets at the time of reproductive failure. Available evidence indicates that this naïve T-cell decline is sensitive to ovarian function and can be reversed in post-reproductive females by transplantation of young ovaries. The restoration of naïve T-cell subsets due to ovarian transplantation was impressive compared with post-reproductive control mice, but represented only a partial recovery of what was lost from 6 months of age. Apparently, the influence of ovarian function on immune function may be an indirect effect, likely moderated by other physiological functions. Estradiol is significantly reduced in post-reproductive females, but was not increased in post-reproductive females that received new ovaries, suggesting an estradiol-independent, but ovarian-dependent influence on immune function. Further evidence for an estradiol-independent influence includes the restoration of immune function through the transplantation of young ovaries depleted of follicles and through the injection of isolated ovarian somatic cells into the senescent ovaries of old mice. While the restoration of naïve T-cell populations represents only a small part of the immune system, the ability to reverse this important